Jamaica : First Review Under the Extended Arrangement Under the Extended Fund Facility and Request for Modification of Performance Criteria. - International Monetary Fund. Western Hemisphere Dept. (Washington, D.C. : International Monetary Fund, 2013)
This paper discusses Jamaica's First Review Under the Extended Arrangement Under the Extended Fund Facility (EFF) and Request for Modification of Performance Criteria. All end-June quantitative conditions and all structural benchmarks were met. The 2013/14 budget is in line with the program. Economic developments remain in line with program assumptions and the macroeconomic outlook and financing scenario remain broadly unchanged from the program approval. The authorities have committed to press ahead with the next round of reforms. Based on the performance to date and the authorities' updated policy intentions, the IMF staff recommends completion of the first review under the EFF.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet